Selective inhibition of immature CD4-CD8+ thymocyte proliferation, but not differentiation, by the thymus atrophy-inducing compound di-n-butyltin dichloride. - Pieters, R H (1994)
Effects of the thymus atrophy-inducing organotin compound di-n-butyltin dichloride (DBTC) on the differentiation and proliferation of immature rat thymocyte subsets were studied in vivo and in vitro. Incubation of freshly isolated CD4-CD8- or immature CD4-CD8+ (characterized as CD4-CD53-) thymocytes with 10(-7) M DBTC for 18 hr did not affect cell recovery or their ability to differentiate to CD4-CD8+ cells and CD4+CD8+ or to CD4+CD8+ cells, respectively. The same treatment decreased the spontaneous as well as the phytohaemagglutinin (PHA)-induced proliferation in both subsets. However, the inhibition of proliferation by DBTC of immature CD4-CD8+, but not of CD4-CD8- thymocytes, appeared to increase with their growth rate. Data show that differentiation of immature thymocytes can proceed independently of proliferation and that DBTC causes thymus atrophy by selectively inhibiting the proliferation of immature CD4-CD8+ thymocytes. Administration to rats of DBTC via the diet for 14 days resulted in an initial decrease of thymoblast number by day 2, followed by a decrease in the total number of thymocytes by day 4. Total thymocyte numbers were lowest on day 7 and did not significantly change thereafter. CD4/CD8 thymocyte subset distributions were similar to controls on day 4, but on day 7 of feeding a marked reduction of the percentage of CD4+CD8+ thymocytes and consequently an increase of the percentages of the three other CD4/CD8 subsets were found. Thereafter, the CD4/CD8 subset distribution recovered, reaching near control values on day 14, despite the very low numbers of thymoblasts and of total thymocytes at that time. Data together indicate that DBTC reduces the production of CD4+CD8+ and mature single-positive thymocytes by selectively inhibiting immature CD4-CD8+ thymocyte proliferation but without affecting the differentiation capacity of these cells. This suggests that thymocyte proliferation and differentiation are separately regulated processes.